Colonizing consent: rape and governance in South Africa's Eastern Cape - Thornberry, Elizabeth (African studies, 2019)
Introduction: Writing the history of rape -- Custom and consent in Xhosaland -- Sex and spiritual power -- Liberalism and the colonial law of sexual violence -- Rape and racial boundaries -- Navigating the politics of consent -- Conclusion: Rape and the postcolony